They Are Not Romeo Pimps, They Are Traffickers: Overcoming the Socially Dominant Discourse to Prevent the Sex Trafficking of Youth. (October 2020) - Merodio, Guiomar; Duque, Elena; Axt Peña, Juan Carlos
Innovative research on sex trafficking is increasingly focusing on the relevance of social relationships in the process of recruitment of young women into sex trafficking. Within the dimension of social interactions, concern is growing about coercive and deceptive intimate relationship–based strategies that traffickers use to recruit young women. To research this recruitment process, the analysis and background on the Language of Desire has allowed us to identify, through qualitative methodology, the standardized use of terms such as Loverboys or Romeo pimps to refer to these traffickers. The extended use of these terms in research, preventive programs, and in general society makes it difficult to reject these violent recruiters and therefore reproduces the vulnerability of young girls to sex traffickers. The qualitative research on sex trafficking presented in this article suggests that they are not Romeo pimps or Loverboys, but traffickers, critically questioning the dominant social discourse imposed on them.